Ion channels in genetic and acquired forms of epilepsy - Lerche, H; Shah, M; Beck, H; Noebels, J; Johnston, D; Vincent, A (2013)
Genetic mutations causing dysfunction of both voltage- and ligand-gated ion channels make a major contribution to the cause of many different types of familial epilepsy. Key mechanisms comprise defective Na+ channels of inhibitory neurons, or GABAA receptors affecting pre- or postsynaptic GABAergic inhibition, or a dysfunction of different types of channels at axon initial segments. Many of these ion channel mutations have been modelled in mice, which has largely contributed to the understanding of where and how the ion channel defects lead to neuronal hyperexcitability. Animal models of febrile seizures or mesial temporal epilepsy have shown that dendritic K+ channels, hyperpolarization-activated cation channels and T-type Ca2+ channels play important roles in the generation of seizures. For the latter, it has been shown that suppression of their function by pharmacological mechanisms or in knock-out mice can antagonize epileptogenesis. Defects of ion channel function are also associated with forms of acquired epilepsy. Autoantibodies directed against ion channels or associated proteins, such as K+ channels, LGI1 or NMDA receptors, have been identified in epileptic disorders that can largely be included under the term limbic encephalitis which includes limbic seizures, status epilepticus and psychiatric symptoms. We conclude that ion channels and associated proteins are important players in different types of genetic and acquired epilepsies. Nevertheless, the molecular bases for most common forms of epilepsy are not yet clear, and evidence to be discussed indicates just how much more we need to understand about the complex mechanisms that underlie epileptogenesis. © 2013 The Physiological Society.